Me and My Future Self: How Perceived Connectedness Shapes Future Thinking and Decision-Making Processes - Fletcher, Daniel (2025)
Just as we sometimes feel like a different person now compared to what we were like in the past, we may also imagine becoming a different person in the future. Accumulating evidence indicates that when individuals feel dissimilar to their possible future self, they more strongly prioritise present over future self-interests in their decision-making. However, less is known about how perceived dissimilarity – or low psychological connectedness – to a future self shapes future thinking and decision-making processes beyond intertemporal trade-offs. In particular, how do people think about future events when anticipating intervening self-change? And what kind of attributes do individuals prioritise when the outcome of their choices will be experienced by a dissimilar future self?